(untitled) (Research, Society and Development, 2025)
Pulmonary pseudotumors comprise a group of non-neoplastic lesions that may mimic pulmonary masses on imaging studies, posing diagnostic and therapeutic challenges. This literature review aims to revisit the concepts, definitions, epidemiology, main etiologies, clinical and radiological findings, as well as diagnostic and therapeutic approaches. Establishing the correct etiological and diagnostic definition of pseudotumors is crucial to avoid unnecessary resections and to ensure appropriate treatment. This review reinforces that the term "pulmonary pseudotumor" encompasses a heterogeneous set of non-neoplastic entities that often mimic tumors on imaging. This heterogeneity explains why differential diagnosis can be challenging.